2016
DOI: 10.1155/2016/6795743
|View full text |Cite
|
Sign up to set email alerts
|

Chromobacterium violaceumSepticaemia and Urinary Tract Infection: Case Reports from a Tertiary Care Hospital in South India

Abstract: Chromobacterium violaceum is a gram negative oxidase positive bacillus that causes human infections infrequently. It is a normal inhabitant of soil and stagnant water of the tropical and subtropical areas. In humans, it can cause infections ranging from life threatening sepsis with metastatic abscesses to skin infections and urinary tract infections. The organism is notoriously resistant to most cephalosporins and Ampicillin. Fluoroquinolones and aminoglycosides show good in vitro susceptibility. High mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 10 publications
(18 reference statements)
1
15
0
Order By: Relevance
“…After 1990, Ciprofloxacin and Carbapenems became the predominant antimicrobial agents [5] [9]. In this case the organism was susceptible to Ciprofloxacin, Trimethoprim-sulfamethoxazole, Doxycycline that corresponds to data obtained from others studies [3] [4] [10]. Also our study demonstrated the sensitivity of C. violaceum to Amoxicillin/Clavulanic acid while Swain [3] and Plant [4] reported resistance of C. violaceum to it.…”
Section: Discussionsupporting
confidence: 84%
“…After 1990, Ciprofloxacin and Carbapenems became the predominant antimicrobial agents [5] [9]. In this case the organism was susceptible to Ciprofloxacin, Trimethoprim-sulfamethoxazole, Doxycycline that corresponds to data obtained from others studies [3] [4] [10]. Also our study demonstrated the sensitivity of C. violaceum to Amoxicillin/Clavulanic acid while Swain [3] and Plant [4] reported resistance of C. violaceum to it.…”
Section: Discussionsupporting
confidence: 84%
“…C. violaceum is generally considered to be of low virulence but septicemia can be deadly. The virulent strains of C. violaceum have elevated levels of superoxide dismutase and catalase which may protect the bacteria from phagocytic attack in humans, in turn leading to fatal infections ( 16 ). Data on antimicrobial susceptibility pattern of this organism is scanty because infections are quite rare.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 17 ] Various antibiotic regimens have been used by various authors, however, ciprofloxacin, co-trimoxazole, gentamicin, and carbapenems have been sensitive in all cases, and ampicillin/amoxicillin have been resistant in almost all cases. [ 2 3 4 5 9 ]…”
Section: Discussionmentioning
confidence: 99%